Upaya Meningkatkan Kemampuan Menghitung pada Materi Perkalian Menggunakan Media Kantong Perkalian pada Siswa Kelas 2 SDI Ulil Albab Kebumen - Sukataman, Sukataman; Khomsatun, Khomsatun; Annafi, Ni’matul Nur; Setiyani, Sulis; Jannah, Vida Nurul (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
This research aims to determine the effectiveness of the multiplication bag learning media in improving the ability to calculate multiplication in class 2 students at SDI Ulil Albab Kebumen for the 2023/2024 academic year. Data collection in this research used interview observation and documentation methods. The background to this research is that the multiplication learning results of class 2 students at SDI Ulil Albab are still below the Minimum Completeness Criteria (KKM). This research uses Classroom Action Research (PTK) with 2 cycles. Each includes implementation planning, observation, evaluation, and reflection. The data collection technique used uses tests. The results show that the implementation of multiplication learning using multiplication bag learning media improved student learning outcomes with an average achievement of 66.66% in cycle I to 88.88% in cycle II. So it can be concluded that the use of multiplication bag learning media can increase second grade students' understanding of the concept of multiplication.